Livestock management ambition in the new and updated nationally determined contributions: 2020-2021: Analysis of agricultural sub-sectors in national climate change strategies - Rose, Sabrina; Khatri-Chhetri, Arun; Dittmer, Kyle; Stier, Milena; Wilkes, Andreas; Shelton, Sadie W; Arndt, Claudia; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Key messages 1) The share of countries with livestock measures in new and updated NDCs has not significantly changed since the previous round of NDCs. 2) 34% of countries included livestock mitigation measures in new and updated NDCs (50 of 148 countries) compared to 35% in the previous NDCs (68 of 192 countries). 3) 36% of countries included livestock adaptation measures in new and updated NDCs (53 of 148 countries) compared to 35% in the previous NDCs (67 of 192 countries). 4) Mitigation priorities included manure management (18% of 148 countries), feed management (16%) and silvopastoralism (10%). Adaptation priorities included breed management (14%), feed management (10%) and silvopastoralism (9%). 5) Among the top 10 countries with the highest mitigation potential for enteric fermentation and manure management, 7 referred to livestock in mitigation measures. 6) Specification of sub-sector actions in NDCs can improve eligibility for climate finance, but this level of detail can reduce countries’ flexibility for meeting their NDC targets and countries often lack affordable, robust monitoring, reporting, and verification (MRV) systems. 7) Livestock commitments that demonstrated high standards, which may indicate options for other countries, included quantified outcomes, reference levels of indicators, mitigation potentials, and policies.